2004
DOI: 10.1097/01.ede.0000142153.28496.d0
|View full text |Cite
|
Sign up to set email alerts
|

Fine Particulate Matter and Wheezing Illnesses in the First Year of Life

Abstract: Air pollution in the form of fine particulates, mostly from vehicular exhaust, may adversely affect infants' respiratory health with potential for chronic effects later in life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
45
0
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(56 citation statements)
references
References 19 publications
7
45
0
4
Order By: Relevance
“…Using Poisson regression and controlling for confounders, the authors concluded that the mortality increment associated with average PM 2.5 levels of 64 g/m 3 was 4.2%, and 4.3% for PM 10 -2.5 (daily average level of 47.3 g/m 3 ). In a cohort study of more than 504 infants younger than 4 months of age in the south of Santiago, Pino et al 50 analyzed the relationship between obstructive bronchitis and PM 2.5 . 50 The authors found that an increment of 10 g/m 3 of PM 2.5 was related to an increase of 5% (CI 0 -9%) of cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using Poisson regression and controlling for confounders, the authors concluded that the mortality increment associated with average PM 2.5 levels of 64 g/m 3 was 4.2%, and 4.3% for PM 10 -2.5 (daily average level of 47.3 g/m 3 ). In a cohort study of more than 504 infants younger than 4 months of age in the south of Santiago, Pino et al 50 analyzed the relationship between obstructive bronchitis and PM 2.5 . 50 The authors found that an increment of 10 g/m 3 of PM 2.5 was related to an increase of 5% (CI 0 -9%) of cases.…”
Section: Discussionmentioning
confidence: 99%
“…In a cohort study of more than 504 infants younger than 4 months of age in the south of Santiago, Pino et al 50 analyzed the relationship between obstructive bronchitis and PM 2.5 . 50 The authors found that an increment of 10 g/m 3 of PM 2.5 was related to an increase of 5% (CI 0 -9%) of cases.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] These high levels pose a serious public health threat. [5][6][7][8][9] Individuals are exposed to air pollution while being outdoors or in various indoor microenvironments. Therefore, measuring air quality in homes, offices, or commercial buildings is very important because individuals spend most of their time indoors.…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that this synergistic effect is due to the carbon particles adsorbing SO 2 , which leaches off slowly, perhaps within macrophages, to recruit leucocytes in airways [19,34,35,36]. Epidemiological data addressing the role of air pollutants at usual levels can only suggest that some pollutants (Sulfur dioxide SO 2 suspended particulates) constituted a risk factor for respiratory infections.…”
Section: Discussionmentioning
confidence: 99%
“…apple juice which might precipitate asthmatic attacks [17]. Hajat et al, Aekplakorn et al and Pino et al studied the effects of fine particulate matter and wheezing illnesses in children and reported stronger effects for Sulfur dioxide (SO2), Nitrogen monoxide (NO) and Nitrogen dioxide (NO2) and concluded that air pollution in the form of fine particulates, mostly from vehicular exhaust might adversely affect infants respiratory health with potential for chronic effects later in life [20,36,37].…”
Section: Discussionmentioning
confidence: 99%